Clinical pharmacology: Developmental path, regulations, education, practical management: Generally and in Serbia - Kastratović Dragana A.; Marković Srđan Z.; Slobodan Janković M. (Srpsko lekarsko drustvo, 2022)
Introduction: After searching literature, Professor of Pharmacology at Cornell University Harry Gold was the first to use the name Clinical Pharmacology in the late 1930s and early 1940s. Topic: Clinical pharmacology is a medical discipline created in the middle of the 20th century, it implies the most effective application of medicine, and it could be said that it is the culmination of all therapeutic approaches in medicine, or simply in the preservation of human health. It is a field that spontaneously appeared in the medical field and from the first moment has the only perspective in the unity of practice and science. The second half of the last century is the time of the beginning of the recognition of specialization in clinical pharmacology as an independent medical discipline, in Europe - first in Sweden, England, Switzerland, Norway in the fifties of the last century, in America also in the same period. In Serbia and Montenegro, we noted the beginning in 1981. Clinical pharmacology is a hospital medical specialization; specialists in clinical pharmacology are doctors who know the most adequate use of drugs, which achieves an optimal therapeutic effect. The basis of clinical pharmacology is pharmacokinetics and pharmacodynamics. The development path of clinical pharmacology spans more than seven decades, and the key moments are the following: concept of bioavailability (Oser et all, 1945), pharmacokinetics (Friedrich Hartmut Dost, 1953), pharmacokinetics / pharmacodynamics (PK/PD) model (De Jongh and Wijnans and Van Gemert and Duyff, 1950), 1960 - 1980 explosion of pharmacokinetic studies and dramatic progress in the field. Pharmacokinetic interactions between drugs become evident and become the subject of many studies: in the 1970s, drug-level monitoring for digoxin, aminoglycosides, phenytoin, theophylline and other drugs began to be implemented in many hospitals. The 1980 - 2000 period is characterized by the advancement of technology, including liquid chromatography, liquid chromatography with a mass detector, and the development of computer technology. What makes clinical pharmacology attractive is the concept of the connection between drug concentration and pharmacodynamic effect, which unites science and practice in achieving a therapeutic effect and more successful medical treatment patients, appeared in the eighties of the last century. In the mid-1980s, Yusko and Boudinot began research linking biochemical mechanisms with pharmacokinetic/pharmacodynamic techniques and leading to their refinement. Conclusion: The development of pharmacology as a profession and science related to the use of drugs spontaneously moved from experimental pharmacology to clinical pharmacology to hospital pharmacology. In order for a clinical pharmacology specialist to really show and prove the useful value of this knowledge, the cooperation of all doctors in teamwork is necessary, as well as cooperation with scientists and cooperation with pharmaceutical magnates. If they find a way for a positive dialogue, the results will become a daily practice. Underline the letter to editors of journals, and alert letters via professional community, meaning be supported and informed. The main developmental goal of hospital pharmacology is to encompass a wide vaiety of specialists and subspecialists, together with strict demands in respecting pharmacoterapy choice, clinical trials law, monitoring side effects of drugs and medical devices. Ffrom authors's experience clinical pharmacologists' duties are clear, however, clinical pharmacology specialists and subspecialists are insufficient. Educating more colleagues is necessery for the future in order to increase presence of clinical pharmacology